Penetapan Waktu Pelaksanaan Banding Terhadap Putusan Pengadilan Tata Usaha Negara Pada Daerah Karakteristik Wilayah Kepulauan - Dezonda Rosiana Pattipawae (Faculty of Law, Universitas Pattimura, 2018)
The party that makes a legal appeal against the case that has been decided by the State Administrative Court is limited by the time to file an appeal to the High Administrative Court. This as stipulated in the provisions of Article 123 of Act Number 5 of 1986 which stipulates the time for legal appeal against the decision of the State Administrative Court is 14 days after the court decision is notified to him legally Determination of 14 (fourteen) times to submit an appeal for parties who are dissatisfied or accept the decision of the State Administrative Court as stipulated in the Provisions of Article 123 of Act Number 5 of 1986 which at the time the decision of the State Administrative Court was read out was not present at the hearing stipulated in the provisions of Article 108 paragraph (2) of Law Number 5 of 1986 and residing in an archipelago such as Maluku Province which has a large area and consists of islands, greatly affects the fulfillment of the timeliness determined to file an appeal . It has an impact on the effectiveness of setting 14 (fourteen) days as the deadline for filing an appeal law. Accordingly, based on these conditions, the stipulation of 14 (fourteen) days to file an appeal law is not effectively applied to regions that are characterized by islands. Only effective in areas with continental characteristics.